PERAN GURU DALAM PENANGANAN PERILAKU ANAK HIPERAKTIF DI TK NEGERI 1 SAMARINDA - Fachrul Rozie; Dita Safitri; Wiwik Haryani (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
The purpose of research is to know: the role of teachers in handling hyperactive child behavior in TK Negeri Pembina 1 Samarinda, the inhibiting factor of teacher in the handling of hyperactive child behavior in TK Negeri Pembina 1 Samarinda, and supporting factor of teacher in handling behaviour of hyperactive children. This method of research is qualitative with a case study approach consisting of two focuses, namely the role of the teacher and child behavior hyperactivity. The results show that hyperactive child behavior has difficulties to focus, unable to sit quietly, perform unmistakable, rebellious activities and could not wait. The teacher's role in child care is hyperactive: as a learning designer, learning artist, learning motivator, mediator learning and inspirational learning. The inhibitory factor in treating hyperactive children is the professionalism of teachers, approaches with hyperactive children, and child behavior. The supporting factors, namely environment, facilities and infrastructure.